The Role of Risk Profile and Time Impatience on the Demand of Peer-to-peer Lending Amidst the Covid-19 Pandemic - Ayif Fathurrahman; Raisa Mukaroma (Journal of Economics Research and Social Sciences, 2023)
This research aims to determine the role of risk profile, time impatience, individual characteristics and location attributes on requests for peer-to-peer lending during the Covid-19 pandemic. The research method is descriptive qualitative with the research subject being the general public of D.I. Yogyakarta Province who have the potential to make peer-to-peer lending. The number of informants used as samples was 96 people selected using purposive sampling method. Data analysis techniques are data reduction, data display, and conclusion data drawing/verification. The results showed that the characteristics of the people of D.I. Yogyakarta Province belonged to the least risk-averse category, and the most patient in accepting long time requests for peer-to-peer lending. Based on the individual characteristics of the community with the least risk avoidance category, namely at the age of 21-30 years, female, living with parents, having 3-6 dependents, not working and with a total income of 1-2 million and according to location attributes the most do not avoid risks in Gunung Kidul Regency. The category of people on individual characteristics that is the most impatient in accepting long periods of time, namely at the ages of 51-60 and 41-50 years, male, owns a private house, has 3-6 dependents, is self-employed, and total income 1 million, and according to the location attribute the most impatient in receiving a long time, namely in Bantul Regency. The results of this study have implications for peer-to-peer lending, namely to better understand the characteristics of the market in DIY. So we need a marketing strategy that is able to convince the market for risk management and improve service quality.